"It's no use crying over spilt milk!": innovation paths in the dairy sector. (13th January 2009) - Massa, Silvia; Testa, Stefania
This paper covers important, not fully explored research topics; namely a broad concept of innovation including not only technology but also social and cultural aspects. It focuses on the processes of innovation in the Italian food industry, namely what kind of innovation Small and Medium Sized Enterprises (SMEs) can afford in a traditional, mature sector and how such innovation can contribute to firms' success. Though some of cross-sectional studies include food, their results are, however, inconclusive regarding the peculiarities of the sector. Two case studies have been developed through several in-depth interviews with key informants and the collection of secondary data. These two case studies regard the dairy sector, which is the primary sector in the Italian food industry in terms of sales. What seems to emerge from the cases is the extreme difficulty that commodity-oriented SMEs face to survive and the need of a reconfiguration of small producers' activities in order to achieve a greater involvement in the local economy, either in the food sector or outside it (e.g. tourism).